Analisis Efektivitas Perawatan Evaporator Plate Fresh Water Generator Type Aqua 125 HW Di Kapal MV CNC Jawa Dengan Metode Fishbone Diagram - Rahman, Rizki Ardika; Imanto, Frenki; Zainuddin, Mochamad; Nugroho, Aziz; Robbi, Shofa Dai (Innovative: Journal Of Social Science Research, 2025)
The Fresh Water Generator (FWG) is a device on ships that converts seawater into freshwater through the processes of evaporation and condensation. FWG is essential for various purposes such as consumption, washing, and engine cooling. This study aims to address three main research questions: what maintenance methods are applied to the FWG evaporator plate, how does the FWG perform before and after maintenance, and how effective is the system after the maintenance is conducted.The research was carried out on the MV CNC Jawa by analyzing the effectiveness of maintenance on the FWG Type AQUA-125-HW evaporator plate through direct observation, interviews with ship crew, and analysis of logbook data. The evaluation used a fishbone diagram to identify the factors contributing to decreased maintenance effectiveness, including human resources, maintenance methods, materials, and machinery.The results show that both preventive and corrective maintenance—such as routine cleaning and the use of Ameroyal chemical agents—successfully improved heat transfer efficiency. Freshwater production increased from 5–8 tons/day to 13 tons/day, energy consumption decreased, and FWG operation became more stable. The evaluation concludes that proper maintenance strategies and crew training are essential in ensuring the reliability of the FWG and the overall operational efficiency of the vessel.